Social Networking Among Health Sciences University Students: Examining Social Network Usage, Social Support, and General Well-Being. - Mahapatra, Neely; Schatz, Mona C. S. (Journal of Human Behavior in the Social Environment)
Social network sites (SNSs) are organized around users who join an internet network to engage in daily discussions and postings. Though research informs us about SNSs usage, no published research addresses the use of social network sites among health science professionals. This study examined the relationship between social network usage, social support, and general well-being among undergraduate and graduate students. This study provides results that identify significant relationships (p< .001) associated with SNS usage and the variables of social support and general well-being among this study population. These results can inform the use of SNSs in university health sciences educational programs.